Protective effects of Bidens pilosa alleviates against alcohol-induced hepatic steatosis in rats: In vivo studies and in silico analysis - Melva Silitonga; Hudson Sidabutar; Hendro Pranoto; Adriana Yulinda Dumaria LumbanGaol; Feimmy Ruth Pratiwi Sipahutar (Elsevier, 2024)
Background: Steatosis has become the critical indicator of the higher alcohol exposure to liver injury. Traditional Chinese medicine, notably Bidens pilosa, is used as anti-inflammatory, antihyperglycemic, and hepatoprotective. This current study aimed to investigate the protective effect of Bidens pilosa leaves ethanolic extract (EEB) against alcohol induced hepatic steatosis. Methods: Using the rat model of alcoholic hepatic steatosis (AHS), this study investigated EEB efficacy through the experimental analysis and in silico method. The animals received EEB at doses of 300 and 600 mg/kg for 42 days in the acute alcoholic experiment. Biochemical analysis and histopathological alteration are examined in alcohol-induced liver rats. Additionally, the pharmacological analysis, molecular docking and dynamic study were evaluated. Results: The results indicated that the EEB has ameliorative effects against hepatic steatosis. It significantly improved hepatic histopathological change, the level of blood glucose, triglyceride, LDL and cholesterol in rats exposed to alcohol. Furthermore, the virtual screening study demonstrated the predominant compounds of EEB might regulate the top core targets linked to AHS, particularly AKT/PIK3CA, MAPK, and MTOR, respectively. Conclusion: Thus, the preventive effect of EEB could be an underlying mechanism for the development of herbal medicine to treat AHS in clinical therapy.